A escola em cena: jogos dramáticos nas aulas de teatro - Galiza, Edmar (Universidade do Vale do Rio dos Sinos, 2011)
This paper aimes to analyze language games played by elementary school students during their rehearsal of plays in theater class. This research uses theoretical models that originate from Ludwig Wittgensteins concepts of the language game, family similarities and life forms, which come mainly from his work Philosophical Investigations. It is also based upon Michel Foucaults ideas of theoretical production, such as discourse and truth games, as well as Jean-Pierre Ryngaerts discussions of dramatic plays. From a theoretical viewpoint, the thesis indicates the possibility of consistently articulating notions of language games, truth games and dramatic plays, as they relate to these authors. The corpus analyzed consists of four dramatic games which were video recorded and later edited, as well as notes taken from observations. To be more specific, this paper demonstrates how, in some dramatic games produced by students gay characters were subject to humiliation, highlighting the students homophobic attitudes.The analysis suggests that theater produced in school is subjugated to the rationality of the school machinery. Essentially, theater that is practiced in school is effectively theater of the school.
Keywords: Teatro e educação; Jogos dramáticos; Homofobia; Escola; Theater and Education; Dramatic games; Homophobia; School; ACCNPQ::Ciências Humanas::Educação